2023
DOI: 10.3390/biomedicines11030821
|View full text |Cite
|
Sign up to set email alerts
|

Updates in KMT2A Gene Rearrangement in Pediatric Acute Lymphoblastic Leukemia

Abstract: The KMT2A (formerly MLL) encodes the histone lysine-specific N-methyltransferase 2A and is mapped on chromosome 11q23. KMT2A is a frequent target for recurrent translocations in acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), or mixed lineage (biphenotypic) leukemia (MLL). Over 90 KMT2A fusion partners have been identified until now, including the most recurring ones—AFF1, MLLT1, and MLLT3—which encode proteins regulating epigenetic mechanisms. The presence of distinct KMT2A rearrangements is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…A prior study reported an association between polymorphisms in both coding and non-coding regions of the MLL1 gene and leukemia [6]. However, this earlier study employed a limited number of in silico tools compared to the present study.…”
Section: Elucidating the Role Of Mll1 Nssnps: Structural And Function...mentioning
confidence: 88%
See 1 more Smart Citation
“…A prior study reported an association between polymorphisms in both coding and non-coding regions of the MLL1 gene and leukemia [6]. However, this earlier study employed a limited number of in silico tools compared to the present study.…”
Section: Elucidating the Role Of Mll1 Nssnps: Structural And Function...mentioning
confidence: 88%
“…MLL1 primarily governs the initiation and elongation of transcription through epigenetic modifications within the promoter regions of target genes [5]. Additionally, the MLL1 protein plays a vital role in the regulation of hematopoietic cell proliferation and differentiation, along with the modulation of the Meis homeobox 1 (MEIS1) and homeobox A (HOXA) gene clusters [6]. When these genes experience irregular regulation, it disrupts proper hematopoietic development, frequently leading to the development of leukemia [7].…”
Section: Elucidating the Role Of Mll1 Nssnps: Structural And Function...mentioning
confidence: 99%
“…6.1. Targeting of KMT2A and DOT1L to Combat Different Forms of Myeloid Leukemia KMT2A also known as lysine methyltransferase 2A is responsible for the establishment of mono-and demethylation of H3K4 via a nonprogressive mechanism [72]. This epigenetic mark has gene-activating effects and is particularly important for early development and hematopoiesis [73,74].…”
Section: Clinical Trials Based On Histone Methyltransferase Activitymentioning
confidence: 99%
“…These KMT2A gene rearrangements can occur in the context of fusion with other gene partners or result from partial tandem duplication within KMT2A (i.e., KMT2A-PTD). KMT2A fusions have been reported in 3% of primary pediatric and adult leukemia as well as 10% of secondary leukemia occurring following treatment with DNA topoisomerase II inhibitors [7][8][9][10][11][12][13]. KMT2A-PTDs are identified in 3-10% of AML cases, particularly in up to 25% of patients with a concurrent trisomy of chromosome 11 [1,4].…”
Section: Introductionmentioning
confidence: 99%